(untitled) (Studies in Ancient Art and Civilisation, 2013)
The city of Nea Paphos is the only ancient city of Cyprus to have preserved much of the painted decoration of its buildings and tombs and the following paper aims to present a fresco that has recently come to light in one of the cemeteries of the city. The newly found painting was discovered on the right-hand side of the entranceway to the funerary chamber of a tomb of Hellenistic and Roman date and may be part of a larger decoration that has been destroyed. A human figure, possibly a young man, is depicted inside a frame created by branches bearing pomegranates. The figure is holding a fruit and is turned to his right, possibly towards another person. Behind him, an open mirror hangs from the wall over something that looks like a funerary monument. Although fragmentary, the scene depicts features that have a deeply symbolic meaning observed for the first time in Paphos. It presents an opportunity to examine new funerary iconography and discuss issues concerning afterlife beliefs in the ancient city.